A Case of Ileocecal IgG4-Related Sclerosing Mesenteritis Diagnosed by Endoscopic Ultrasound-Guided Fine Needle Aspiration using Forward-Viewing Linear Echoendoscope - Yuichi Takano; Fumitaka Niiya; Takahiro Kobayashi; Eiichi Yamamura; Naotaka Maruoka; Tomoko Norose; Nobuyuki Ohike; Masatsugu Nagahama (Case Reports in Gastrointestinal Medicine)
A 25-year-old woman had undergone removal of a cryptogenic tumor in the left maxillary sinus 1 year prior to presentation. The patient experienced abdominal pain for 4 days with repeated vomiting episodes; therefore, she was transferred to our hospital by an ambulance. Contrast-enhanced computed tomography revealed a 3-cm tumor in the ileocecal region, which caused small bowel obstruction. Contrast imaging of the ileus tube showed extrinsic compression of the ileocecal region. Forward-viewing linear echoendoscope revealed an irregular hypoechoic tumor measuring 3 cm outside the gastrointestinal tract. Using a 25G needle, endoscopic ultrasound-guided fine needle aspiration (EUS–FNA) was performed. Pathological finding was an inflammatory fibrous tissue with diffuse lymphoplasmacytic infiltration, with more than 10 IgG4-positive cells detected in a high-power field. Re-examination of a pathology specimen of the maxillary sinus tumor provided by the previous attending physician revealed that the inflammatory tissue had diffuse lymphoplasmacytic infiltration, which were accompanied by storiform fibrosis and obliterative phlebitis. Immunostaining revealed more than 50 IgG4-positive cells in a high-power field, a finding suggestive of IgG4-related disease. The serum IgG4 level was 21 mg/dl, which was within the normal range. Treatment was initiated with prednisolone at a dose of 50 mg/day, and the dose was later tapered off. CT and MRI performed 2 months later showed complete disappearance of the ileocecal tumor. The final diagnosis was asynchronously occurring IgG4-related maxillary sinusitis and sclerosing mesenteritis.